Liquid parties, dense populism. (December 2019) - Urbinati, Nadia
Before proceeding, I would like to clarify briefly two interpretative premises, one methodological and one normative, which sustain my argument. Understanding the transformations facing constitutional democratic societies is a demanding task. These transformations, whose multiple causes are socio-economic not merely political, reflect on the one hand in the decline of mass party form of organization and on the other in the success of populism as not simply a movement of contestation but as a ruling power. In this article, I will suggest that the successes of populism are connected to the decline of organized parties, the pillar of constitutional democracy as it emerged after 1945. It is impossible to predict whether populism will succeed in becoming the new form of democracy. It is, however, certain that contemporary representative governments are facing astonishing mutations and the decline of the party form of representative unification of claims and ideas is one of them. My argument relies upon a phenomenology of populism as a movement that is strong in proportion as organized parties are weak, which actually capitalizes on a revolt against intermediary bodies such as parties. 1